2021
DOI: 10.1155/2021/9349738
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Raindrop Size Distribution in Typhoon Nida (2016) before and after Landfall in Southern China from 2D Video Disdrometer Data

Abstract: During the passage of Typhoon Nida, the raindrop size distribution parameters, the raindrop spectra, the shape and slope (μ–Λ) relationship, the radar reflectivity factor, and rain rate (Z–R) relationship were investigated based on a two-dimensional (2D) video disdrometer in Guangdong, China, from August 1 to 2, 2016. Due to the underlying surface difference between the ocean and land, this process was divided into two distinct periods (before landfall and after landfall). The characteristics of raindrop size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This suggests that SST played a primary role in pCO 2sea during the initial limited time period of Typhoon Merbok. Furthermore, there was no significant slowdown in the temperature-induced pCO 2sea relative to non-temperature factors during the second step of Typhoon Nida (figure 8), indicating that SST may not only be affected by deeper water but may also be influenced by other factors such as heavy rainfall, which could cause a decrease in SST (Deng et al 2019, Feng et al 2021.…”
Section: Temporal Changes In Pco 2sea and Co 2 Fluxes In In Northern ...mentioning
confidence: 94%
“…This suggests that SST played a primary role in pCO 2sea during the initial limited time period of Typhoon Merbok. Furthermore, there was no significant slowdown in the temperature-induced pCO 2sea relative to non-temperature factors during the second step of Typhoon Nida (figure 8), indicating that SST may not only be affected by deeper water but may also be influenced by other factors such as heavy rainfall, which could cause a decrease in SST (Deng et al 2019, Feng et al 2021.…”
Section: Temporal Changes In Pco 2sea and Co 2 Fluxes In In Northern ...mentioning
confidence: 94%
“…The strong upward motion and the vertical circulation configuration of low-level convergence and high-level divergence are favorable for the forced uplifting of warm and wet water vapor in the lower levels to above the convective condensation height, which further favors the development of short-term heavy rainfall. Raindrop spectra are an essential parameter in cloud precipitation physics [29]. Therefore, we analyze the raindrop spectrum distribution characteristics from the DSG5 precipitation phenomenon instrument in Longmen national weather station (Figure 9), which is near the heavy precipitation area.…”
Section: High Efficiency Of Water Vapor Condensationmentioning
confidence: 99%
“…Compared with the average raindrop spectrum during May-June from 2017 to 2020 (gray dash line in Figure 9b), we find that the distribution of the average raindrop spectrum from 0400-0800 CST in this process (black dash line in Figure 9b) is similar, but the number concentration of particles with a diameter less than 7 mm is obviously larger during this process. Moreover, due to the small range of extreme heavy rainfall in this process (about 10 km radius from Long- Raindrop spectra are an essential parameter in cloud precipitation physics [29]. Therefore, we analyze the raindrop spectrum distribution characteristics from the DSG5 precipitation phenomenon instrument in Longmen national weather station (Figure 9), which is near the heavy precipitation area.…”
Section: High Efficiency Of Water Vapor Condensationmentioning
confidence: 99%
“…Many studies have shown that there are obvious temporal and spatial variations in RSD characteristics in terms of rainfall rate and type due to diferences in climate background, geographical location, and atmospheric condition [22][23][24][25][26][27][28][29]. Based on observations of two diferent disdrometers and radar retrievals, Bringi et al [1] analyzed RSD characteristics under various climate regimes and found that there are signifcant sea-land dissimilarities in convective rainfall.…”
Section: Introductionmentioning
confidence: 99%